2014
DOI: 10.1158/1541-7786.mcr-13-0641
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-26a/b Regulate DNA Replication Licensing, Tumorigenesis, and Prognosis by Targeting CDC6 in Lung Cancer

Abstract: Cancer is characterized by mutations, genome rearrangements, epigenetic changes, and altered gene expression that enhance cell proliferation, invasion, and metastasis. To accommodate deregulated cellular proliferation, many DNA replication-initiation proteins are overexpressed in human cancers. However, the mechanism that represses the expression of these proteins in normal cells and the cellular changes that result in their overexpression are largely unknown. One possible mechanism is through miRNA expression… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 39 publications
2
50
0
Order By: Relevance
“…NCBP2 and SHMT2 were significantly reduced both as transcript and protein, while MTHFD2 was reduced as transcript but not protein, after miR160 transfection (Supplementary Figure 6). Human microRNA regulation of CDC6 has already been described as a mechanism of prevention of lung cancer formation20, while PYCR1 and MTHFD2 have been shown to be required for breast tumorigenesis in vitro 21.…”
Section: Resultsmentioning
confidence: 99%
“…NCBP2 and SHMT2 were significantly reduced both as transcript and protein, while MTHFD2 was reduced as transcript but not protein, after miR160 transfection (Supplementary Figure 6). Human microRNA regulation of CDC6 has already been described as a mechanism of prevention of lung cancer formation20, while PYCR1 and MTHFD2 have been shown to be required for breast tumorigenesis in vitro 21.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, bladder cancer patients with Cdc6 up-regulation have significantly shorter disease free survival time than those with lower Cdc6 expression. These results are consistently with previous researches in other type of cancers, such as oral squamous cell carcinoma [19], lung carcinomas [18, 29], cervical carcinoma [17], gallbladder carcinoma [30], prostate cancer [20]. Considering that Cdc6 is normally absent in quiescent and differentiated cells, it could be specific markers for cancer cells.…”
Section: Discussionsupporting
confidence: 91%
“…Many miRNAs with known function are involved in cell proliferation, apoptosis, differentiation and migration, which are commonly implicated in cancer development. 15 The increasing amounts of data have shown that miRNAs can act as oncogenes or tumor suppressors and participate in cancer development and progression. 16,17 Studies on miRNAs and tumors started with large-scale screening of microarray to detect the differentially expressed miRs between tumor tissues and normal tissues aiming at developing new strategies in tumor diagnosis and treatment in clinic.…”
Section: Discussionmentioning
confidence: 99%